A Cross-Cultural Examination of the Criminal Sentiments Scale–Modified - Mazher, Sania (Criminal justice and behavior, 2022)
Research has demonstrated that criminal attitudes are a primary predictor of criminal conduct; hence, measuring attitudes is important. The Criminal Sentiments Scale–Modified (CSS-M) is a widely used measure of criminal attitudes; however, its psychometric properties have been established primarily on Western samples and there is a pressing need to translate the scale into other languages. Hence, the objective of this research was to translate CSS-M into the Urdu language and validate it. This objective was achieved in three studies on samples of young adults. In Study I, the scale was translated and its cross-language validation was established. In Study II, the factor structure of the CSS-M was examined through CFA. In Study III, interscale correlations and gender differences were examined. Findings demonstrated that CSS-M is a reliable and valid instrument when assessing attitudes toward crime in the Pakistani sample.